ANALISIS FUNDAMENTAL DAN NILAI INTRINSIK PERUSAHAAN BERBASIS SEKTOR INDUSTRI KONSUMSI - Arsyad Sumantika; Ganda Sirait; Elva Susanti; Welly Sugianto (Universitas Putera Batam, 2021)
One of the goals of investment is to get a benefit in the form of profits and funds saved. Based on official data compiled on the IDX's official website, company shares on the Indonesia Stock Exchange can be divided into 9 sectors, one of which is consumption industry. The consumption sector is a general sector used by the general public consisting of the food and beverages, the pharmaceuticals, househol, and houseware sector. Investors must choose which shares to buy or sell. Investors can analyze a stock using fundamental and intrinsic analysis. The purpose of this study is to analyze issuers that have the 10 largest market capital in the industrial consumption sector, then analyze the performance of issuers using a fundamental approach EPS, PE Ratio, Price to Sales, Return on Assets, Return on Equity, Return on Capital Employed, and Interest Coverage. The final stage is to determine the undervalued and overvalued companies using 4th quarter 2020. Based on 10 companies that have the largest market capital in the consumer industry sector (UNVR, HMSP, ICBP, KLBF, GGRM, MYOR, INDF, SIDO, MLBI, and KAEF) can be concluded that (1) The highest EPS ratio is GGRM and the lowest is KAEF, the lowest PER Ratio is GGRM and the highest is KAEF, the lowest PS Ratio is KAEF and the highest is UNVR, the highest ROA ratio is MLBI and the lowest is KAEF, the highest ROE ratio is MLBI and the lowest is KAEF , the highest ROCE ratio is MLBI and the lowest is KAEF, the highest IC ratio is HMSP and the lowest is KAEF; and (2) There are 2 issuers in the undervalued category, namely GGRM and HMSP; while included in the overvalued category is KAEF.